Optimization of photodegradation of acid blue 1 dye on aluminosilicate supported Cu doped TiO2 magnetic nanocatalyst using response surface methodology - Fatemeh Mollaie; Mahdieh Afroomand; Najmeh Ahmadi; Nezamaddin Mengelizadeh; Davoud Balarak (Scientific Reports)
Abstract In this study, the magnetic TiO2/Cu/aluminosilicate (MCTA) catalyst was synthesized through a two-step process using the hydrothermal and solvothermal methods. The synthesized materials underwent comprehensive characterization using various analytical techniques. These materials were subsequently applied for the effective elimination of Acid Black 1 dye (AB1). To establish robust correlations among these influential parameters, the research adopted the Box–Behnken design (BBD) within the framework of RSM. This approach ensures a systematic and thorough exploration of the interplay between various variables in the photocatalytic degradation process. In this study, sunlight was utilized as an energy source for the degradation process. The degradation of AB1 reached its peak efficiency under the following optimal conditions: catalyst mass of 0.75 g/L, AB1 concentration of 37.5 mg/L, pH of 3, and a contact time of 45 min. The efficiency, based on the model prediction, was 98.9%, while experimental results showed a 99.1% efficiency. Dark adsorption tests were also conducted, revealing that the dye degradation rate through the photocatalytic process was 18–22 times higher compared to the adsorption process at different concentrations. Toxicity tests revealed that the remaining AB1 in the aquatic environment lost its antibacterial activity after undergoing the studied process. The scavenger experiment provided confirmation that successful photodegradation of AB1 is attributed to the indispensable contribution of both •OH and •O2 −. Additionally, MCTA demonstrated outstanding cycle stability in the photocatalytic degradation of AB1. MCTA emerges as a dependable sunlight-responsive heterostructure photocatalyst with significant potential for the photodegradation of pollutants in wastewater treatment.